Mulch effect on successive crop yields and soil carbon in Tonga. (27th December 2016) - Manu, V.; Whitbread, A.; Blair, G.
Abstract: Intensification of crop production in Tonga has resulted in a move to mechanical soil preparation, often with a rotary hoe, and a consequent loss in both chemical physical fertility. An experiment was conducted on a clay loam soil (Typic Argiudoll) on the Forestry Vaini Research Station, Tongatapu Island, Tonga, to investigate the effect of a once‐off application of mulch on yield and quality of watermelon, maize and capsicum grown in rotation over a 1‐yr period. The treatments applied were a nonmulched control, transparent plastic and 200‐mm‐thick applications of locally available coconut sawdust, guinea grass and mature coconut fronds. The fresh fruit yield of watermelon in all the mulch treatments was 7.3–18.1% higher than in the nonmulched control. There was no significant effect of thick vegetative mulch on maize grain dry matter yield; however, the maize yield was significantly lower in the transparent plastic mulch than in the other treatments. The capsicum marketable fruit yield in the following crop was increased by 49–73% in all the vegetative mulch treatments compared to the non‐mulched control. The higher crop yields with the vegetative mulch were attributed to the measured lower soil temperatures and higher soil moisture in these treatments. There was no effect of mulch on soil total N (TN), but soil total C (TC), soil labile C (LC) and the carbon management index (CMI) were increased.